Manifestaciones químicas del micromercurialismo en personal de clinica odontológica de la Universidad Nacional Mayor de San Marcos - Taboada V., Manuel (2001)
The evaluation of the analyze of Laboratory and clinical it determined the presence of mercury intoxication in the personal file of Dental Clinical Universidad Nacional Mayor de San Marcos. That labory in direct contac with dental mercury. The clinicals manifestations was: disorder memory 23% /46, irritability 22% /46, celphagia 18%/46. The levels of mercury to fluctuate over 25 and 70 ug/m3. Time of the exposition six months.